2007
DOI: 10.1097/ta.0b013e31806842a1
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Procedures Before Emergency Department Thoracotomy: “Scoop and Run” Saves Lives

Abstract: The performance of prehospital procedures in critical, penetrating trauma victims had a negative impact on survival after EDT in our study population. Paramedics should adhere to a minimal or "scoop and run" approach to prehospital transportation in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 31 publications
4
92
0
4
Order By: Relevance
“…24 Studies also have shown that in cases of penetrating trauma, decreased time to definitive care is associated with improved survival outcomes. [25][26][27] Conclusions The current case series demonstrates the life-saving potential for law enforcement personnel trained and equipped under current TCCC/C-TECC tactical casualty care guidelines. Although originally developed to save the lives of wounded combat personnel, in the civilian sector, the training is more likely to save victims rather than law enforcement personnel.…”
Section: Limitationsmentioning
confidence: 99%
“…24 Studies also have shown that in cases of penetrating trauma, decreased time to definitive care is associated with improved survival outcomes. [25][26][27] Conclusions The current case series demonstrates the life-saving potential for law enforcement personnel trained and equipped under current TCCC/C-TECC tactical casualty care guidelines. Although originally developed to save the lives of wounded combat personnel, in the civilian sector, the training is more likely to save victims rather than law enforcement personnel.…”
Section: Limitationsmentioning
confidence: 99%
“…Appeared a likely source of this increased risk of indirect central neurologic injury. CSI iatrogenia may have facilitated indirect neurologic injury by negatively impacting the "ischemic penumbra" [2][3][4][5][6]15,[22][23][24]27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid mortality associated with vascular and airway injuries emphasizes the importance of immediately treating these lifethreatening injuries before addressing concerns about cervical spine instability [5,[17][18][19][20][21][22]. Transport delays for CSI vary from an average of 8-30 mins [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Es claro que tiempos largos y la inadecuada reanimación prehospitalaria (reanimación agresiva con cristaloides) se asocia a peores resultados e impacto negativo en la sobrevida. 29 En el presente estudio debemos considerar varias limitaciones. Es un estudio retrospectivo de una única institución, donde la mayoría de los pacientes corresponden a los alrededores de una de las localidades con los índices más altos de violencia en Bogotá.…”
Section: Análisis De Asociación Con La Mortalidad Hospitalariaunclassified